MAKNA “SEPATU” PADA NAZAR DESI DALAM NOVEL GURU AINI: KAJIAN PSIKOANALISIS SIGMUND FREUD - Hanifah Yulia Sari (Vokal: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is to reveal the inner conflict of the main character in the Novel Guru Aini. A source of this research is a novel Guru Aini, written by Andrea Hirata in 2020. The data were collected using library techniques. The data that has been collected is then analyzed using Freud's psychoanalytic theory. This novel tells about the journey of the main character named Desi Istiqomah in fulfilling her obsession. The purpose of this study was to determine the personality of the main character, namely Desi Istiqomah. The result of this research is that the personalities described in the novel are one of the solutions to his efforts to fulfill his own obsession. While the use of shoes in the vows spoken by Desi Istiqomah is described between the continuity that must exist in life, especially between science and reason.